(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: This research aims to investigate the impact of board of directors’ characteristics on integrated reporting and its reflection on Iraqi economic units value. To achieve this, the research relied on the deductive approach with regard to the theoretical aspect of the research, by relying on Arabic and foreign books, theses, dissertations, articles, and another site related to the research subject. in the practical aspect, this research relied on inductive approach by analyzing financial reports of commercial banks listed in Iraqi stock exchange in 2021. This research reached a set of conclusions, the most important of which is the size of director board and the number of board meetings have positive and significant impact in integrated reporting , the percentage of women in director board have negative and insignificant effect in integrated reporting, the integrated reporting have positive and significant effect in firm value ,the indirect effect of director board characteristics in firm value by integrated reporting is more than direct effect of board characteristics in firm value . The research came out with a set of recommendations, the most important of which is increase the size of director board and the number of board meetings because they increase integrated reporting which increase firm value . decrease the percentage of women in the board of director to increase integrated reporting. Increase integrated reporting in order to increase firm value.